2021
DOI: 10.1186/s43166-021-00080-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between carpal tunnel syndrome and trigger finger: a clinical and electrophysiological study

Abstract: Background Carpal tunnel syndrome is a prevalent mononeuropathy. Trigger finger is a flexor stenosing tenosynovitis. The aim of the study was to assess the concomitant occurrence of carpal tunnel syndrome and trigger finger in the same hand among patients presented with idiopathic carpal tunnel syndrome or idiopathic trigger finger. The study included 110 hands (75 patients) presented with carpal tunnel syndrome or trigger finger and 60 asymptomatic hands (46 apparently healthy individuals). Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In this meta-analysis, the incidence of post-CTR TF was calculated based on the individual-based counting method in the five included studies, which reported a total of 9207 CTR surgeries and 827 cases of TF, resulting in an overall incidence of 7.7% (range: 5.2–12.2%). Many studies have reported the association between CTR and TF, but the spontaneous consent rate for carpal tunnel syndrome and TF ranged from 9.76 to 61% 2 , 9 , 30 , which was relatively wide and imprecise. Therefore, we determined the causal relationship between CTR and TF.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, the incidence of post-CTR TF was calculated based on the individual-based counting method in the five included studies, which reported a total of 9207 CTR surgeries and 827 cases of TF, resulting in an overall incidence of 7.7% (range: 5.2–12.2%). Many studies have reported the association between CTR and TF, but the spontaneous consent rate for carpal tunnel syndrome and TF ranged from 9.76 to 61% 2 , 9 , 30 , which was relatively wide and imprecise. Therefore, we determined the causal relationship between CTR and TF.…”
Section: Discussionmentioning
confidence: 99%